2017
DOI: 10.7326/m16-1131
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescribing for Nonbacterial Acute Upper Respiratory Infections in Elderly Persons

Abstract: Ontario Ministry of Health and Long-term Care, Academic Medical Organization of Southwestern Ontario, Schulich School of Medicine and Dentistry, Western University, and Lawson Health Research Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
97
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 48 publications
6
97
2
3
Order By: Relevance
“…We did not examine specific provider factors beyond clinical service. However, previous studies have found that physician specialty, age or level of career, gender, patient volume, and country of training were associated with antibiotic prescribing for URIs [8,9,11,28].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We did not examine specific provider factors beyond clinical service. However, previous studies have found that physician specialty, age or level of career, gender, patient volume, and country of training were associated with antibiotic prescribing for URIs [8,9,11,28].…”
Section: Discussionmentioning
confidence: 84%
“…Finally, we did not formally review each antibiotic prescription for the URI to assess appropriateness. However, we chose diagnosis codes that correspond to conditions for which antibiotics would generally be considered inappropriate, which is consistent with the approach taken in other studies [3,[7][8][9][10][11][12][13]. In addition, we reviewed diagnoses of sinusitis and found that appropriate use [6,29] in these cases contributed minimally to total antibiotic use in the cohort.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another strength of our study was the high number of postgraduate years of the participants. The more years in a doctor's experience, the more likely he/she is to prescribe inappropriate antibiotics for viral RTIs . It is noteworthy that this course was both satisfactory and helpful for experienced doctors, who were the relevant target population of such a workshop.…”
Section: Discussionmentioning
confidence: 93%
“…In 2010-11, 18% of prescriptions in doctors' offices and emergency departments for adults aged 65 and older were considered unnecessary 25 , and overuse of macrolides for respiratory tract infections is well documented in adults 26 . Antibiotics were inappropriately prescribed for 46% of low-risk older adults presenting with nonbacterial acute upper respiratory tract infections, and 70% of prescriptions were for broad-spectrum agents, such as macrolides 27 . Appropriate antibiotic use is particularly important because of the high risk of adverse drug events and complications that can result from drug-drug interactions in this age group 6,8 .…”
Section: Discussionmentioning
confidence: 99%